Missense MED12 variants in 22 males with intellectual disability: From nonspecific symptoms to complete syndromes. Issue 1 (22nd October 2022) - Maia, Nuno; Ibarluzea, Nekane; Misra‐Isrie, Mala; Koboldt, Daniel C.; Marques, Isabel; Soares, Gabriela; Santos, Rosário; Marcelis, Carlo L. M.; Keski‐Filppula, Riikka; Guitart, Miriam; Gabau Vila, Elisabeth; Lehman, April; et al.
Abstract: We describe the phenotype of 22 male patients (20 probands) carrying a hemizygous missense variant in MED12 . The phenotypic spectrum is very broad ranging from nonspecific intellectual disability (ID) to the three well‐known syndromes: Opitz–Kaveggia syndrome, Lujan–Fryns syndrome, or Ohdo syndrome. The identified variants were randomly distributed throughout the gene ( p  = 0.993, χ 2 test), but mostly outside the functional domains ( p  = 0.004; χ 2 test). Statistical analyses did not show a correlation between the MED12 ‐related phenotypes and the locations of the variants ( p  = 0.295; Pearson correlation), nor the protein domain involved ( p  = 0.422; Pearson correlation). In conclusion, establishing a genotype–phenotype correlation in MED12 ‐related diseases remains challenging. Therefore, we think that patients with a causative MED12 variant are currently underdiagnosed due to the broad patients' clinical presentations.